Landscape as a factor of the city vertical dominants system formation - Beskorovaina, Iryna (Видавництво Львівської політехніки, 2013)
The influence of landscape on the vertical dominants system formation is described. The interrelation of landscape specifics with town-building composition, the influence of landscape on the visual perception of vertical dominants and on the compositional scheme of vertical dominants formation are investigated.
Keywords: landscape; town-building composition; the vertical dominants system of city; terrain; water; visual perception